Effect of sample orientation and initial microstructures on the dynamic recrystallization of a Magnesium alloy - Gao, P.; Zhu, S.Q.; An, X.H.; Xu, S.Q.; Ruan, D.; Chen, C.; Yan, H.G.; Ringer, S.P.; Liao, X.Z. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2017)
Strongly textured Mg–3Al–1Zn (wt%) alloy samples with a high density of twins cut from three directions were used to investigate the effect of crystallographic orientation on dynamic recrystallization (DRX). The samples were deformed under a high strain rate at 300°C. The high strain rate allows rapid dislocation accumulation, making DRX possible at relatively low strain values. We demonstrate that crystallographic orientation and the initial twins have significant effects on DRX because of the different activities of dislocations and their interactions with twin boundaries. This research provides a potential pathway for improving the formability of Mg alloys.